An update to monoclonal antibody as therapeutic option against COVID-19 - Paroma Deb; Md. Maruf Ahmed Molla; K.M. Saif- (Elsevier, 2021)
With the number of Coronavirus Disease 2019 (COVID-19) cases soaring worldwide and limited vaccine availability for the general population in most countries, the monoclonal antibody (mAb) remains a viable therapeutic option to treat COVID-19 disease and its complications, especially in the elderly individuals. More than 50 monoclonal antibody-related clinical trials are being conducted in different countries around the world, with few of them nearing the completion of the third and fourth phase clinical trial. In view of recent emergency use authorization (EUA) from the FDA (Food and Drug Administration) of casirivimab and imdevimab, it is of importance that mAbs, already used to treat diseases such as Ebola and respiratory syncytial virus (RSV) infection, are discussed in scientific communities. This brief review discusses the mechanism of action and updates to clinical trials of different monoclonal antibodies used to treat COVID-19, with special attention paid to SARS-CoV-2 immune response in host cells, target viral structures, and justification of developing mAbs following the approval and administration of potential effective vaccine among vulnerable populations in different countries.